RNF186 regulates EFNB1 (ephrin B1)-EPHB2-induced autophagy in the colonic epithelial cells for the maintenance of intestinal homeostasis. Issue 10 (3rd October 2021) - Zhang, Huazhi; Cui, Zhihui; Cheng, Du; Du, Yanyun; Guo, Xiaoli; Gao, Ru; Chen, Jianwen; Sun, Wanwei; He, Ruirui; Ma, Xiaojian; Peng, Qianwen; Martin, Bradley N.; et al.
ABSTRACT: Although genome-wide association studies have identified the gene RNF186 encoding an E3 ubiquitin-protein ligase as conferring susceptibility to ulcerative colitis, the exact function of this protein remains unclear. In the present study, we demonstrate an important role for RNF186 in macroautophagy/autophagy activation in colonic epithelial cells and intestinal homeostasis. Mechanistically, RNF186 acts as an E3 ubiquitin-protein ligase for EPHB2 and regulates the ubiquitination of EPHB2. Upon stimulation by ligand EFNB1 (ephrin B1), EPHB2 is ubiquitinated by RNF186 at Lys892, and further recruits MAP1LC3B for autophagy. Compared to control mice, rnf186 -/- and ephb2 -/- mice have a more severe phenotype in the DSS-induced colitis model, which is due to a defect in autophagy in colon epithelial cells. More importantly, treatment with ephrin-B1-Fc recombinant protein effectively relieves DSS-induced mouse colitis, which suggests that ephrin-B1-Fc may be a potential therapy for human inflammatory bowel diseases. Abbreviations : ACTB: actin beta; ATG5: autophagy related 5; ATG16L1: autophagy related 16 like 1; ATP: adenosine triphosphate; Cas9: CRISPR associated protein 9; CD: Crohn disease; CQ: chloroquine; Csf2 : colony stimulating factor 2; Cxcl1 : c-x-c motif chemokine ligand 1; DMSO: dimethyl sulfoxide; DSS: dextran sodium sulfate; EFNB1: ephrin B1; EPHB2: EPH receptor B2; EPHB3: EPH receptor B3; EPHB2 K788R : lysine 788 mutated to arginine in EPHB2; EPHB2 K892R : lysine 892 mutated to arginine in EPHB2; ER: endoplasmic reticulum; FITC: fluorescein isothiocyanate; GFP: green fluorescent protein; GWAS: genome-wide association studies; HRP: horseradish peroxidase; HSPA5/BiP: heat shock protein family A (Hsp70) member 5; IBD: inflammatory bowel diseases; Il1b : interleukin 1 beta; Il6 : interleukin 6; IRGM:immunity related GTPase M; i.p.: intraperitoneally; IPP: inorganic pyrophosphatase; KD: knockdown; KO: knockout; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; MTOR: mechanistic target of rapamycin kinase; NOD2: nucleotide binding oligomerization domain containing 2; PI3K: phosphoinositide 3-kinase; PtdIns3K: class III phosphatidylinositol 3-kinase; RNF186: ring finger protein 186; RNF186 A64T : alanine 64 mutated to threonine in RNF186; RNF186 R179X : arginine 179 mutated to X in RNF186; RPS6: ribosomal protein S6; Tnf : tumor necrosis factor; SQSTM1: sequestosome 1; Ub: ubiquitin; UBE2D2: ubiquitin conjugating enzyme E2 D2; UBE2H: ubiquitin conjugating enzyme E2 H; UBE2K: ubiquitin conjugating enzyme E2 K; UBE2N: ubiquitin conjugating enzyme E2 N; UC: ulcerative colitis; ULK1:unc-51 like autophagy activating kinase 1; WT: wild type.